Mapping Teenage Rebellion, Autonomy, and Parent–Child Conflict in Southeast Asian Families: A Scoping Review - Rudyard LeRoy A. Benemerito; Zsui M. Gabriana; Venice Ann F. Venturina; Myla M. Arcinas (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Teenage rebellion is a familiar lay term, yet how it is conceptualized and studied within Southeast Asian families—settings shaped by collectivist values, filial piety, and strong parental authority—remains unclear. This scoping review mapped the available evidence as a necessary first step toward more focused empirical work. Following the methodological framework of Arksey and O’Malley as refined by Levac and colleagues and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews, two databases were searched for peer-reviewed, English-language studies published between January 2000 and January 2025 on adolescents aged 13 to 19 years living with their families in Southeast Asia. Records were screened against pre-specified eligibility criteria, and data were charted in response to five research questions. Ten studies from six countries (Singapore, Thailand, Malaysia, the Philippines, Vietnam, and Indonesia) were included. Only two studies named rebellion directly; most used proxy constructs such as risk taking, conduct problems, aggression, children beyond control, and emotional and behavioral problems. Family conflict, weak parental monitoring or support, peer influence, and socioeconomic strain were the most consistently reported contributing factors. Manifestations centered on defiance, withdrawal, and conflict, whereas outcomes ranged from distress and risk behavior to, in supportive families, prosocial behavior and well-being. Designs were overwhelmingly cross-sectional. Southeast Asian research approaches adolescent rebellion obliquely, through related constructs and predominantly cross-sectional designs. The field would benefit from clearer conceptualization, qualitative work centering adolescents’ voices, longitudinal designs, culturally grounded frameworks, and more country-specific evidence.